2012
DOI: 10.1287/mnsc.1110.1508
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Business and Household Sector Innovation in Consumer Products: Findings from a Representative Study in the United Kingdom

Abstract: In a first survey of its type, we measure development and modification of consumer products by product users in a representative sample of 1,173 UK consumers aged 18 and over. We estimate this previously unmeasured type of innovation to be quite large: 6.1% of UK consumers -nearly 2.9 million individuals -have engaged in consumer product innovation during the prior three years. In aggregate, consumers' annual product development expenditures are more than 1.4 times larger than the annual consumer product R&D e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(107 citation statements)
references
References 32 publications
7
99
0
1
Order By: Relevance
“…In the case of consumer innovation, for example, publics aim to solve particular real-life problems, bringing innovation closer to societal needs that are defined from the bottom-up (von Hippel 2017). In higher income countries, consumer innovation represents a significant portion of a nation's innovation activities (Bengtsson 2015;De Jong 2011;Kuusisto et al 2013;Ogawa and Pongtanalert 2011;von Hippel, de Jong, and Flowers 2012). Examples are wide-ranging, including children's products developed by parents (Shah and Tripsas 2007), software and sport-related goods (Jeppesen and Frederiksen 2006;Lüthje 2004), and therapies for chronic diseases (Oliveira et al 2015).…”
Section: Civil Society Engagement and Bottom-up Innovationmentioning
confidence: 99%
“…In the case of consumer innovation, for example, publics aim to solve particular real-life problems, bringing innovation closer to societal needs that are defined from the bottom-up (von Hippel 2017). In higher income countries, consumer innovation represents a significant portion of a nation's innovation activities (Bengtsson 2015;De Jong 2011;Kuusisto et al 2013;Ogawa and Pongtanalert 2011;von Hippel, de Jong, and Flowers 2012). Examples are wide-ranging, including children's products developed by parents (Shah and Tripsas 2007), software and sport-related goods (Jeppesen and Frederiksen 2006;Lüthje 2004), and therapies for chronic diseases (Oliveira et al 2015).…”
Section: Civil Society Engagement and Bottom-up Innovationmentioning
confidence: 99%
“…Indeed, one of the largest sources of OI that firms can draw upon is the activities and knowledge of individual users, consumers, clients or customers (Laursen and Salter 2006;von Hippel, de Jong, and Flowers 2012;Piller and West 2014). Individual users may directly contribute to the OI process of firms by communicating their needs and preferences, based on their use experience, while they may also use and innovate their goods in contexts outside of the firm's domain (von Hippel 1988(von Hippel , 2005Bogers, Afuah, and Bastian 2010).…”
Section: Extra-organizational Level Of Analysismentioning
confidence: 99%
“…In his recent research, von Hippel introduces some measures to quantify the importance of users in the innovation process and suggests that billions of dollars are spent annually by users to improve products and make them better suited to their needs [von Hippel et al, 2011[von Hippel et al, , 2012. With respect to scale, von Hippel's surveys found that millions of users collectively spend billions of dollars every year on developing and modifying consumer products.…”
Section: Role Of User Communities In Developing Innovationmentioning
confidence: 99%
“…In the UK, 2.9 million people (6.1% of the population) spend a total of $5.2 billion annually on this activity. In the US, 16 million people (5.2% of the US population) collectively spend $20.2 billion, and in Japan 4.7 million people (3.7% of the population) collectively spend $5.8 billion to create and modify user products for their own use [von Hippel et al, 2012;Ogawa, Pongtanalert, 2011]. However, valuable consumerrelated knowledge is widely dispersed, so hearing only one voice might in fact be of little relevance.…”
Section: Role Of User Communities In Developing Innovationmentioning
confidence: 99%